Labour nationality and religion - Connolly, James (Dublin: New Books, 1973)
"by James Connolly Bibliotheek François VercammenBeing a discussion of the Lenten Discourses against socialism delivered by Father Kane, S.J. in Gardiner Street Church, Dublin, 1910"